Primary school teacher outcomes from online professional development for physical literacy: A randomised controlled trial. (July 2022) - Simpson, Aaron; Rosenberg, Michael; Ward, Brodie; Thornton, Ashleigh L.; Derbyshire, Amanda; Jackson, Ben
Abstract: Introduction: Primary (or elementary) school teachers are often relied upon to provide children with opportunities for physical literacy development; however, many of these teachers feel they lack the skills to effectively promote or 'teach' physical literacy. We examined the effects of an online physical literacy professional development program—relative to receiving widely-available online resources or continuing with 'normal' practice—on primary school teachers' physical literacy knowledge and application. Methods: A parallel three-arm randomised controlled trial in which 92 primary school teachers were assigned to (a) an online professional development program designed to support teachers' physical literacy instructional skills ('intervention'), (b) receive widely-available online physical literacy resources ('comparison'), or (c) a typical practice 'control' condition. Data were collected at baseline and following the four-week intervention period. The primary outcome was teachers' physical literacy knowledge and application; secondary outcomes included teachers' self-reported perceptions of confidence, values, and barriers. Between-group differences were assessed using the intention-to-treat principle with analysis of covariance accounting for demographic factors and baseline differences in the focal outcome. Results: Teachers in the intervention arm scored significantly higher on post-intervention physical literacy knowledge and application than their counterparts in both the control ( d  = .47, p  = .044) and comparison ( d  = 0.87, p  = .007) arms. This pattern of differences was also observed for teachers' value of physical literacy, autonomy support, and perceived personal barriers. Conclusion: To the best of our knowledge, this is the first adequately powered randomised controlled trial to demonstrate improvements in physical literacy instructional outcomes as a result of primary school teacher participation in targeted online professional development. Highlights: Participation in online professional development improves physical literacy instructional outcomes. Outcomes include increased confidence and application of knowledge, and fewer barriers. Less support for benefits of online resources only, some positive outcomes revealed.